Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.nuclphysa.2003.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical understanding of the nuclear incompressibility: where do we stand?

Abstract: The status of the theoretical research on the compressional modes of finite nuclei and the incompressibility K ∞ of nuclear matter, is reviewed. It is argued that the recent experimental data on the Isoscalar Giant Monopole Resonance (ISGMR) allow extracting the value of K ∞ with an uncertainity of about ± 12 MeV. Non-relativistic (Skyrme, Gogny) and relativistic mean field models predict for K ∞ values which are significantly different from one another, namely ≈ 220-235 and ≈ 250-270 MeV respectively. It is s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The effect of pairing correlations is, in general, more important in the constrained calculations than in the scaled ones, especially in half-filled major shell nuclei, as is the case of 112 Table VIII. To compare with the experiment, we use as representative the constrained energyĒ 1 , which estimates the energy of the centroid in a very precise way at least in the case of the nucleus in 208 Pb [95,96] (see also [90,91]. This is a general tendency shown by mean-field models of different nature [97,98]. Several attempts to explain this behavior have been proposed in the past such as the density dependence of the incompressibility in neutron rich-matter [99] or different types of pairing interactions [48].…”
Section: Excitation Properties Of the Bcp Energy Density Functionalmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of pairing correlations is, in general, more important in the constrained calculations than in the scaled ones, especially in half-filled major shell nuclei, as is the case of 112 Table VIII. To compare with the experiment, we use as representative the constrained energyĒ 1 , which estimates the energy of the centroid in a very precise way at least in the case of the nucleus in 208 Pb [95,96] (see also [90,91]. This is a general tendency shown by mean-field models of different nature [97,98]. Several attempts to explain this behavior have been proposed in the past such as the density dependence of the incompressibility in neutron rich-matter [99] or different types of pairing interactions [48].…”
Section: Excitation Properties Of the Bcp Energy Density Functionalmentioning
confidence: 99%
“…The fact that effective mean-field models with different values of K 0 can give similar values of E GMR in 208 Pb has actually been a general puzzle in the past (see Refs. [95,97] and references therein). The reason is the proportionality between E GMR and the square root of K 0 found by Blaizot [100] for Gogny forces.…”
Section: Excitation Properties Of the Bcp Energy Density Functionalmentioning
confidence: 99%
“…What come out from these calculations is a globally too large value of the compressibility modulus K even there is some numerical uncertainty in its determination and even if its extraction is not free of ambiguity in the context of relativistic theories [21]. Removing the contact term (i.e., taking the Orsay prescription for the treatment of the pion and tensor rho exchanges) has the advantage to reduce the C parameter to a value closer to the lattice estimate, C ≃ 1.25, but the incompressibillity K still increases by about 15 − 20 MeV.…”
Section: A Infinite Symmetric Mattermentioning
confidence: 99%
“…The E1 strength consists of two components which have been observed from light to heavy nuclei [5,8,22,23,28]. The high-energy component is the compression mode [29], while it has been suggested that the low-energy component might be a "toroidal giant dipole mode" [30,31]. The E1 distributions were fit with two Gaussians and parameters obtained are shown in [4].…”
Section: -3mentioning
confidence: 99%